Kegiatan Penguatan Karakter Siswa Madrasah Ibtidaiyah Melalui Etika Bermedia Digital dilingkungan Sekolah MI Nurul Ikhlas Tambak Sawah - Dewi Nur 'Aini (JPPMI: Jurnal Pelayanan dan Pemberdayaan Masyarakat Indonesia, 2026)
In the context of information technology, Madrasah Ibtidaiyah students engage in community education activities related to digital access ethics. Increasing access to digital media does not always follow literacy, which can lead to negative consequences including unhealthy communication, hoaks, and cyberattacks. Because of this, the goal of this activity is to improve student character through digital media education in the context of MI Nurul Ikhlas Tambak Sawah. Pengembangan masyarakat berbasis aset (ABCD) is the approach used, which encourages the utilization of local resources and potential through the following phases: penemuan, impian, desain, definisi, and tujuan. Pengamatan partisipatif between students, teachers, and school administrators is used to collect data. This activity consists of a Ramadan webinar that encourages interactive discussions, learning environments, and role-playing about how to use digital media in a responsible manner. The activity's results indicate that students' understanding of the importance of ethics when using digital media has increased. In the digital world, students start learning how to interact with others, share information before sharing it, and communicate with others. In addition, this practice helps create a more positive digital culture in the classroom. In order to increase digital literacy and muda character traits, this practice needs to be continued. This study highlights the importance of helping students develop strong character traits in the digital age